Overview of exercise addiction - early detection for early intervention - Khairun’naim Khairuddin; Muhammad ‘Adil Zainal Abidin; Hazwani Hanum Hashim; Azwanis Abdul Hadi (Penerbit UMS, 2025)
Exercise has been proven to have many significant positive physical, mental and social effects. It makes our body healthier, reduces stress levels and improves relationships with others. However, not much is known about the negative effects of exercise as the benefits of exercise are more visible. In excess, some people who could develop one of the substantial negative effects of exercise called exercise addiction. The complications of exercise addiction can be seen in the form of injuries, stress, anxiety and social relationship problems. Early detection of a person with high risk of exercise addiction can prevent its complications by instituting an early intervention. This review aims to examine the available literature on exercise addiction as well as to elicit available psychometric tools that can be used to detect exercise addiction.